Evaluating Scholars' Impact and Influence: Cross-sectional Study of the Correlation Between a Novel Social Media-Based Score and an Author-Level Citation Metric - Oliveira J e Silva, Lucas; Maldonado, Graciela; Brigham, Tara; Mullan, Aidan F; Utengen, Audun; Cabrera, Daniel (JMIR Publications, 2021)
BackgroundThe development of an author-level complementary metric could play a role in the process of academic promotion through objective evaluation of scholars' influence and impact. ObjectiveThe objective of this study was to evaluate the correlation between the Healthcare Social Graph (HSG) score, a novel social media influence and impact metric, and the h-index, a traditional author-level metric. MethodsThis was a cross-sectional study of health care stakeholders with a social media presence randomly sampled from the Symplur database in May 2020. We performed stratified random sampling to obtain a representative sample with all strata of HSG scores. We manually queried the h-index in two reference-based databases (Scopus and Google Scholar). Continuous features (HSG score and h-index) from the included profiles were summarized as the median and IQR. We calculated the Spearman correlation coefficients (ρ) to evaluate the correlation between the HSG scores and h-indexes obtained from Google Scholar and Scopus. ResultsA total of 286 (31.2%) of the 917 stakeholders had a Google Scholar h-index available. The median HSG score for these profiles was 61.1 (IQR 48.2), and the median h-index was 14.5 (IQR 26.0). For the 286 subjects with the HSG score and Google Scholar h-index available, the Spearman correlation coefficient ρ was 0.1979 (P<.001), indicating a weak positive correlation between these two metrics. A total of 715 (78%) of 917 stakeholders had a Scopus h-index available. The median HSG score for these profiles was 57.6 (IQR 46.4), and the median h-index was 7 (IQR 16). For the 715 subjects with the HSG score and Scopus h-index available, ρ was 0.2173 (P<.001), also indicating a weak positive correlation. ConclusionsWe found a weak positive correlation between a novel author-level complementary metric and the h-index. More than a chiasm between traditional citation metrics and novel social media-based metrics, our findings point toward a bridge between the two domains.